Der Handel zwischen Russland und den Baltischen Staaten: Pfadabhängigkeit oder wirtschaftliche Rationalität? - Markus, Raul; Veebel, Viljar (Estonian Discussions on Economic Policy, 2017)
In recent 25 years, trade relation between Russia and the Baltic countries have been often challenged by constant setbacks. However, despite it the Baltic countries have been interested in developing trade relations with Russia. The article focuses on the question, whether this pattern could be related to the path dependence approach or to specific economic factors, derived from the economic growth and business cycle theories and the small open economy models. On this basis, it also discusses the outlook for the normalisation of trade relations, assuming that sanctions will be eliminated at a certain moment in time. The authors argue that in theory, the normalisation of trade relations is possible if: a) the cooperation between the EU and Russia will reach the stage that brings significant benefits to the Baltic countries, or b) risks related to Russia’s erratic behaviour on the international stage will decrease significantly. Both developments seem to be rather unlikely in short run.